2017
DOI: 10.1101/125724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Index switching causes “spreading-of-signal” among multiplexed samples in Illumina HiSeq 4000 DNA sequencing

Abstract: Illumina-based next generation sequencing (NGS) has accelerated biomedical discovery through its ability to generate thousands of gigabases of sequencing output per run at a fraction of the time and cost of conventional technologies. The process typically involves four basic steps: library preparation, cluster generation, sequencing, and data analysis. In 2015, a new chemistry of cluster generation was introduced in the newer Illumina machines (HiSeq 3000/4000/X Ten) called exclusion amplification (ExAmp), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
201
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(210 citation statements)
references
References 17 publications
5
201
4
Order By: Relevance
“…Previous work has suggested that index switching is occurring for 1-10% of reads depending on 131 factors during library preparation and sequencing (Sinha et al 2017). This low level means that, 132 for our dataset, at a single locus, an allele acquired because of index switching is likely to only 133 have one read, given moderate overall read depth.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Previous work has suggested that index switching is occurring for 1-10% of reads depending on 131 factors during library preparation and sequencing (Sinha et al 2017). This low level means that, 132 for our dataset, at a single locus, an allele acquired because of index switching is likely to only 133 have one read, given moderate overall read depth.…”
mentioning
confidence: 96%
“…With the central role that sequencing 34 plays, it is alarming that a recent preprint suggests increased index switching on the new HiSeq 35 4000 and HiSeq X machines (Sinha et al 2017). 36…”
Section: Introduction 27 28mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that capture or sequencing failed for these wells, so they were not used for variance estimation. In addition, we examined the effect of index switching (Sinha et al 2017) in each data set generated on the HiSeq 4000 and found it to be negligible (Supplemental Material, Section 3; Supplemental Fig. 13).…”
Section: Data Analysis For the Mixture Experimentsmentioning
confidence: 99%
“…Multiplexing samples, specifically biased MDA'd samples, for sequencing on the Illumina platform, however, can cause significant 'bleed over' between poolmates. For example, Sinha et al [34] showed that 5-10% of reads can be assigned to the wrong sample based on low levels of index-free primers present in the multiplexed pool, when using the HiSeq platform. More stringent library cleanup procedures, the use of dual indexes [35] and quality filtering [36] are all methods that can reduce this effect.…”
Section: Assessment Of Poolmate Cross-contaminationmentioning
confidence: 99%